En clase con "El Principito" (Journal of Parents and Teachers, 2014)
The author celebrates the centenary of the writer Antoine de Saint-Exupéry. In this way, it takes a look at the life of the author of The Little Prince, detailing the most significant aspects of his life.  The article also includes a section on classroom activities related to the theme of the work, as well as to the characters that appear in it
Keywords: The Little Prince; Education; Reading; Biography